A Philosophical Examination of the English Laws Relating to Assisted Suicide: Resurrecting Emotion - Taylor, Kiera (Kent Law Review, 2014)
This study seeks to jurisprudentially analyse the statutory English laws relating to assisted suicide, so as to advance a justifiable re-articulation of their moral framework. Currently based on emotionless principles, that framework necessarily denies ethics. Particular attention is paid to a conceptual study of assisted suicide and particularly the notion of ‘assistance’. This analysis is made against a background of the traditional Natural Law, which is supported as the correct, albeit under-developed legal theory defining the scope and logic of English suicide laws. Knowledge and reason jointly constitute the correct yardstick by which morality and therefore justice in this area should be measured; not solely the latter. The re-articulation of this framework shall be primarily achieved by resurrecting human emotions through a study of fine art, supported by English common law developments so as to distinguish various extra-jurisdictional anomalies. It shall be concluded that the laws in this area, as they are currently enacted, are immoral and therefore unjust and legalisation through Parliament (with the necessary safeguards) is justifiable in the eyes of the traditional Natural Lawyer. The dissertation on which this article is based won the Kent Law School Hallett Dissertation Prize for best law dissertation in 2013.